Integrative cross‐tissue analysis unveils complement‐immunoglobulin augmentation and dysbiosis‐related fatty acid metabolic remodeling during mammalian aging - Zhang, Feng; Li, Rong; Liu, Yasong; Liang, Jinliang; Gong, Yihang; Xiao, Cuicui; Cai, Jianye; Wang, Tingting; You, Qiang; Zhang, Jiebin; Chen, Haitian; Xiao, Jiaqi; et al. (iMeta, 2025)
Aging‐related decline and adaptation are complex, multifaceted processes that affect various tissues and increase risk of chronic diseases. To characterize key changes in cross‐tissue aging, we performed comprehensive proteomic and metabolomic analyses across 21 solid tissues and plasma samples, alongside shotgun metagenomic profiling of fecal microbial communities in young and aged mice. Our findings revealed widespread aging‐rewired chronic inflammation, characterized by complement system activation in plasma and universal immunoglobulins accumulation across multiple solid tissues. This inflammatory remodeling significantly enhanced vulnerability to aging‐related tissue injury. Moreover, we identified organ‐specific and organ‐enriched proteins with high functional specificity. Among these, aging‐related proteins were closely linked to disorders arising from lipid metabolism dysfunction. Analysis of multi‐tissue metabolomic and fecal metagenomic profiles revealed that aging significantly disrupted inter‐tissue metabolic coupling, activities of polyunsaturated fatty acids metabolism, and gut microbiota homeostasis. Aged mice exhibited a marked decrease in Escherichia and an increase in Helicobacter, strongly correlating with alterations in omega‐3 and omega‐6 fatty acid abundances. Through multi‐omics integration, we identified key molecular hubs driving organismal responses to aging. Collectively, our study uncovers extensive aging‐associated alterations across tissues, emphasizing the interplay between systemic inflammation and dysbiosis‐driven fatty acid remodeling. These findings provide deeper insights into the development of healthy aging from a cross‐tissue perspective. Our study provides a comprehensive multi‐omics profile of aging, integrating proteomic, metabolomic, and metagenomic analyses across diverse tissues and plasma. We identified the synergistic amplification of the circulating complement system and tissue‐wide immunoglobulin accumulation as key molecular drivers of inflammaging. Furthermore, we uncovered gut microbiota dysbiosis, characterized by a significant decrease in Escherichia and an increase in Helicobacter, which contributes to lipid metabolic reprogramming, particularly the dysregulation of polyunsaturated fatty acid metabolism across multiple tissues. By elucidating the intricate interplay between inflammaging and dysbiosis‐induced fatty acid metabolic remodeling in mammalian aging, our study highlights promising gero‐protective targets and pathways that could mitigate aging‐related diseases and enhance health span. These insights pave the way for developing novel therapeutic strategies to promote healthy aging. Highlights Integrated proteomic, metabolomic, and metagenomic analyses revealed tissue‐spanning and tissue‐specific changes during mammalian aging. Systemic inflammaging was triggered by the accumulation of immunoglobulins in solid tissues and the activation of circulating complement system. Aging‐related remodeling of tissue‐resolved proteostasis and fatty acid pathways contributed to disorders related to lipid metabolism dysfunction. Dysbiosis of gut microbiota, involving Escherichia and Helicobacter, was significantly associated with dysregulated metabolism of polyunsaturated fatty acids.